2004
DOI: 10.1136/gut.53.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclooxygenase 2, microsomal prostaglandin E synthase 1, and EP receptors is increased in rat oesophageal squamous cell dysplasia and Barrett's metaplasia induced by duodenal contents reflux

Abstract: Background and aim: It is known that bile acids can induce mucosal injury, stimulate cell proliferation, and promote tumorigenesis. A large body of genetic and biochemical evidence indicate that the biosynthetic pathway of prostaglandin E 2 (PGE 2 ) may play an important role in human and rodent tumours. Therefore, we examined the expression pattern of cyclooxygenase 1 (COX-1), COX-2, and microsomal prostaglandin E synthase 1 (mPGES-1), as well as EP receptor subtypes in rat oesophageal lesions induced by duod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 46 publications
4
40
1
Order By: Relevance
“…2, B and D). Up-regulation of EP receptors has been reported in rat Barrett's metaplasia, a premalignant lesion of esophageal adenocarcinoma, induced by duodenal contents reflux (Jang et al, 2004). In this study, we provide direct evidence that the EP2 receptor plays a predominant role in the mediation of the stimulatory effect of PGE 2 in esophageal squamous cell carcinoma.…”
Section: Ep2 Receptor Mediates Mitogenic Action Of Pge 2 263supporting
confidence: 61%
“…2, B and D). Up-regulation of EP receptors has been reported in rat Barrett's metaplasia, a premalignant lesion of esophageal adenocarcinoma, induced by duodenal contents reflux (Jang et al, 2004). In this study, we provide direct evidence that the EP2 receptor plays a predominant role in the mediation of the stimulatory effect of PGE 2 in esophageal squamous cell carcinoma.…”
Section: Ep2 Receptor Mediates Mitogenic Action Of Pge 2 263supporting
confidence: 61%
“…In our model, the squamous epithelium showed significant hyperplasia and papillary bulge, which was also found in the animal models of other studies (27)(28)(29)(30)(31). However, to our knowledge, this is the first study to show the formation of keratin pearls and keratocysts caused by epithelial hyperplasia in an animal model for chronic bile reflux.…”
Section: Glandular Stomachsupporting
confidence: 81%
“…Other studies have found that chronic bile reflux could cause Barrett's esophagus and esophageal adenocarcinoma (27,29,32); however, only 1 case of intestinal metaplasia and no adenocarcinoma occurred for up to 1 year in our rats. This difference in the results may also be attributable to the different operations performed in the studies.…”
Section: Glandular Stomachcontrasting
confidence: 69%
“…This indicates a role for PGE 2 in tumorigenesis (Jabbour et al, 2001;Cohen et al, 2003;Kamei et al, 2003;Jang et al, 2004;Kawata et al, 2006;Shi et al, 2006).…”
Section: Cancermentioning
confidence: 95%